2016
DOI: 10.1007/s12199-016-0512-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of toe pinch force to other muscle strength parameters in men with type 2 diabetes

Abstract: Objective The aim of this study was to explore the relations between toe pinch force and other muscle strength parameters in male patients with type 2 diabetes mellitus. Methods A total of 40 men with type 2 diabetes (age: 53.4 ± 13.1 years, duration of diabetes: 8.5 ± 8.1 years) who needed exercise training were enrolled in this crosssectional study. We evaluated the clinical parameters and 4 muscle strength parameters, which were toe pinch force, handgrip strength, isometric knee extension force, and isometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Reduced strength and volume in some muscle groups (especially those in the foot) are observed in patients with diabetes and diabetic neuropathy than in patients with diabetes mellitus but not suffering from diabetic neuropathy [2,26,27]. Furthermore, the patients with diabetes mellitus (especially with neuropathy) have more toe and foot deformities than persons without diabetes mellitus [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced strength and volume in some muscle groups (especially those in the foot) are observed in patients with diabetes and diabetic neuropathy than in patients with diabetes mellitus but not suffering from diabetic neuropathy [2,26,27]. Furthermore, the patients with diabetes mellitus (especially with neuropathy) have more toe and foot deformities than persons without diabetes mellitus [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic retinopathy, nephropathy, and polyneuropathy will be diagnosed based on JDS guidelines. As described in our previous studies 20) , diabetic polyneuropathy is defined by the presence of at least two of the following symptoms: (1) dysesthesia, pain, and/or loss of sensation, (2) decreased or absence of Achilles tendon reflex, and (3) decreased vibratory sensation (≤ 10 sec).…”
Section: Clinical and Laboratory Measurementsmentioning
confidence: 95%
“…We will measure the handgrip strength and KEF. Handgrip strength will be measured using a handgrip dynamometer (T.K.K.5401, Takei Scientific Instruments Co., Ltd., Niigata, Japan), as described previously 20) . The subject will be in the standing position with the upper limb relaxed at the side, elbow fully extended, and palm inward.…”
Section: Assessment Of Muscle Strength Skeletal Muscle Mass Motor Fmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of Checker-kun (Nissin Sangyo Inc., Saitama, Japan) for measurement of toe pinch force was recently developed and established. We have also reported that the toe pinch force equipment has high reproducibility [3], and the measurements were significantly correlated with other muscle strength parameters such as handgrip strength, isometric knee extension force, and isometric ankle dorsiflexion force in patients with type 2 diabetes mellitus (DM) [4]. In addition, the toe pinch force in patients with type 2 DM was significantly lower than that in patients without type 2 DM, and diabetic polyneuropathy was fundamentally associated with lower toe pinch force in patients with type 2 DM [5].…”
Section: Introductionmentioning
confidence: 99%